2010
DOI: 10.1017/s0031182010001150
|View full text |Cite
|
Sign up to set email alerts
|

Testing temporal stability of the larval digenean community in Heleobia conexa (Mollusca: Cochliopidae) and its possible use as an indicator of environmental fluctuations

Abstract: Larval digeneans have been proposed as indicators of abundance and diversity of vertebrate and other hosts as well as environmental disturbances. To evaluate its response to environmental changes and its potential use as an indicator of environmental fluctuations, the temporal stability of the community of larval digeneans in Heleobia conexa was comparatively analysed in 4 separate years (1996, 1999, 2004 and 2005) in Mar Chiquita coastal lagoon (Buenos Aires province, Argentina). In total, 4579 specimens of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 55 publications
(122 reference statements)
2
24
0
Order By: Relevance
“…references in Ostrowski de Núñez 2001, Merlo and Etchegoin 2010). In Heleobia australis from Bahía Blanca estuary, however, we found only one species of heterophyid: A.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…references in Ostrowski de Núñez 2001, Merlo and Etchegoin 2010). In Heleobia australis from Bahía Blanca estuary, however, we found only one species of heterophyid: A.…”
Section: Discussionmentioning
confidence: 49%
“…In H. conexa from the Mar Chiquita coastal lagoon, the individual prevalences were also low, except for those of a notocotylid, a heterophyid, and two microphallids (Microphallus szidati and M. simillimus); but none of them present at higher levels than 9% (Merlo and Etchegoin 2010). Microphallus szidati was not found in the Bahía Blanca estuary-where, as mentioned previously, marine conditions prevail (Freije and Marcovecchio 2004)-probably because this species is, rather, a brackish and freshwater trematode, having been described as a parasite of H. conexa in the Mar Chiquita coastal lagoon and of H. parchappii in a freshwater environment from Buenos Aires province.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Positive relationship between bird abundance and the presence of larval digenean parasitizing snail hosts on small to medium spatial scales were found by several studies (e.g. Curtis and Hurd 1983;Hechinger and Lafferty 2005;Koprivnikar et al 2007;Merlo and Etchegoin 2011). In addition, Prinz et al (2010) observed that the temperature increase coincides with a large number of definitive hosts and with a consequent increase in parasite prevalence in the mollusc hosts.…”
Section: Discussionmentioning
confidence: 80%